Frequency of Complications Related to Real Time Ultrasound Guided Renal Biopsy in A Tertiary Care Hospital. - Qadri, Ghulam Abbas; Riaz, Muhammad Mohsin; Sabir, Omer; Dilawar, Mubashar; Said, Hafiz Usman (Pakistan Journal of Kidney Diseases, 2021)
Introduction: Renal biopsy has a pivotal role in establishing diagnosis, aiding in therapeutic decisions and prognostic assessment in diseases affecting native kidneys or transplants. Renal biopsies are being performed for more than a century and considered the gold standard. Although renal biopsy is considered to be a safe procedure still it includes risk for potential complications such as pain, hematuria and hematoma. Proper patient preparation and evaluation is mandatory to avoid post biopsy complications. Back up of interventional radiology and surgery is important to deal with any complications related to renal biopsy. We conducted a study in consecutive kidney biopsy patients to observe the frequency of complications associated with the procedure. Methods: patients undergoing renal biopsy were evaluated for baseline characteristics and after informed consent underwent renal biopsy. All patients were observed for 24 hours for any complications and a repeat ultrasound and hemoglobin were done before discharge. It was a descriptive case series. Results: In our study, out of 340 cases, mean age was 50.55+9.29 years, 48.82%(n=166) were male. The frequency of complications in renal biopsy was recorded as 11.47%(n=39) had pain, 3.23%(n=11) had hematuria while 7.94%(n=27) had hematoma. Conclusion: Kidney Biopsy is safe and in our study pain and hematoma were found to be the most frequent complications of renal biopsy similar to the international data.